Decreased levels of T follicular helper (CD4+CXCR5+) cells and CD27+CD38+ and CD27+CD38− B cells in ankylosing spondylitis patients correlate with markers of inflammation. (23rd November 2022) - Lejon, Kristina; Hellman, Urban; Kumar, Anjani; Forsblad‐d'Elia, Helena
Abstract: The purpose of this study was to study CD4+CXCR5+ T follicular helper (TFH) cells, CD27+CD38+ plasmablasts and CD27+CD38− memory B cells, as well as disease‐related factors in patients with ankylosing spondylitis (AS) from northern Sweden. Peripheral blood mononuclear cells (PBMC) from 50 patients with AS (mean age 52 ± 9 years, 66% men, 100% HLA‐B27 positive) and 50 pairwise matched blood donor controls (mean age 54 ± 9 years, 66% men) were stained with antibodies for CD27, CD38, CD19, CD3, CD4 and CXCR5 markers and analysed by flow cytometry. Patients with AS were examined with spinal x‐ray for radiographic alterations (mSASSS), and plasma levels of C‐reactive protein, erythrocyte sedimentation rate, as well as selected proinflammatory and regulatory cytokines were determined. Physical mobility, function and disease activity were registered by BASMI, BASFI and ASDAS‐CRP, BASDAI, respectively. Comparing AS patients and controls pairwise, we observed a 56% reduction of TFH cells in PBMCs from AS patients ( P  = .000008). Furthermore, a 20%‐30% reduction in plasmablasts and B memory cells ( P  ≤ .002 and P  ≤ .007, respectively) was observed. In female patients, negative correlations between ESR and TFH, plasmablasts and B memory cells were observed; Rs = −0.551, P  ≤ .02; Rs = −0.476, P  ≤ .05 and Rs = −0.522, P  ≤ .03, respectively. In addition, positive correlations between the regulatory cytokine IL‐10 and the proportion of B cells, IL‐22, and the proportion of plasmablasts as well as a negative correlation between levels of the proinflammatory cytokine IL‐6 and TFH were detected. Our observations indicate a role of an aberrant humoral immune response related to inflammation in AS.